IntensityCheck – The light measuring app for microscope performance checks and consistent fluorescence imaging - Dormann, Dirk (PloS one, 2019)
Quantitative fluorescence imaging is an essential tool in biomedical research. It requires consistent and repeatable conditions such as constant sample illumination. Even on a confocal microscope this can usually only be achieved by using an external laser power meter. By combining low-cost wireless Arduino based light sensors with an easy to use Android smartphone app we provide microscope users with a simple but powerful tool to maintain sample illumination for quantitative imaging, for tracking the intensity, stability and alignment of the light sources and for comparing microscope performance.